KEBIJAKAN PENGEMBANGAN KONSEP SEA GATE INTERNATIONAL (SGI) GUNA MEWUJUDKAN KEMANDIRIAN MARITIM INDONESIA - Kumalasari, Galuh Wahyu (Faculty of Law, University of Muhammadiyah Malang, 2016)
The idea of the Indonesian Autonomy of maritime shows that Indonesia is not yet self-sufficient in the maritime sector. This simple statement is a major issue that must be resolved. Indonesia has ratified the United Nations Convention on the Law of the Sea (UNCLOS) through Act No. 17 of 1985, but there has been no significant progress to outperform the competition with countries in the world. The concept of Sea Gate International (SGI) to implement the development and improvement of both quantity and quality is the main port to adjust international standards should be a realistic and optimistic step in order to realize the independence of maritime in Indonesia. Foreign ships will be more and more anchored in Indonesia and will improve the optimization of human resource development, science and technology as well as product quality and service the maritime sector. Narrates deeper, the existence of Indonesia as SGI will be one important factor to improve the position of Indonesia in world geoeconomic and geopolitical map. Policy Planning seriously need to be realized in the long term development plan, making clear the direction and the benchmark every year running